A review of ROS based autonomous driving platforms to carry out automated driving functions - Carvalho, Marcus Vinícius Leal de (2022)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Campus Joinville, Programa de Pós-Graduação em Engenharia e Ciências Mecânicas, Joinville, 2022.